Creating Green Bond Markets : Insights, Innovations, and Tools from Emerging Markets - Sustainable Banking Network (International Finance Corporation, Washington, DC, 2018)
This report has been developed by IFC and the Climate Bonds Initiative (CBI) on behalf of the Sustainable Banking Network (SBN) Green Bond Working Group. Established in 2012, SBN is a unique community of financial sector regulatory agencies and banking associations from emerging markets committed to advancing sustainable finance in line with international good practice. The Network facilitates the collective learning of members and supports them in policy development and related initiatives to create drivers for sustainable finance in their home countries. SBN now represents 35 countries and over US$43 trillion of bank assets in emerging markets. Responding to strong interest from SBN members in the global green bond trend, a Green Bond Working Group was formed in October 2017 as a Community of Practice on local green bond market development. Comprised of SBN member country representatives and observers from 21 countries and 30 organizations active or with a strong interest in creating green bond markets, the Working Group has the following broad objectives: to enhance collective knowledge and develop technical resources to support members in developing green bond markets; to support the integration of environmental, social and governance (ESG) factors into all stages of green bond issuance and reporting; and to support SBN members to develop and deepen green bond markets through awareness raising, capacity building, and knowledge sharing. The activities of the Working Group have been divided into two phases: mapping of the current status and lessons learned from national, regional and global green bond guidance, standards and practices; and development of practical technical tools to support green bond market development.